2014
DOI: 10.1590/1983-084x/13_026
|View full text |Cite
|
Sign up to set email alerts
|

Pimenta pseudocaryophyllus (Gomes) Landrum: aspectos botânicos, ecológicos, etnobotânicos e farmacológicos

Abstract: RESUMO:Pimenta pseudocaryophyllus (Gomes) Landrum é a única espécie representante brasileira deste gênero de Myrtaceae. Tem sido popularmente utilizada no tratamento de diversas enfermidades, assim como condimento e aromatizante de bebidas, por seu sabor muito similar ao cravo-da-índia. Em menor escala, é empregada em carpintaria e na arborização urbana. Diversos autores analisaram a composição química do óleo essencial da espécie em diferentes regiões do Brasil, encontrando eugenol, metileugenol, (E) metiliso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results of our study demonstrated that the leaf extracts of M. atropurpureum caused 100% mortality after 24 h of treatment. It has been reported that the essential oils extracted from the leaves of Pimenta pseudocaryophyllus have larvicidal activity against A. aegypti (CL 50 = 44.09 ppm) 27 . Numerous studies have reported the larvicidal activity of essential oils extracted from various plants.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study demonstrated that the leaf extracts of M. atropurpureum caused 100% mortality after 24 h of treatment. It has been reported that the essential oils extracted from the leaves of Pimenta pseudocaryophyllus have larvicidal activity against A. aegypti (CL 50 = 44.09 ppm) 27 . Numerous studies have reported the larvicidal activity of essential oils extracted from various plants.…”
Section: Discussionmentioning
confidence: 99%
“…Genus Pimenta Lindley belongs to family Myrtaceae, subfamily Myrtoideae, and to Myrteae tribe, comprises 15 species (+6 varieties) [38], was described by John Lindley in 1821 as the type species "Pimenta officinalis." Its name derives from the Latin pigmentum, "color" of the verb to paint, a name destined for spices, in association with the characteristics of the fruit of that type [40,41]; it is characterized by fragrant shrubs or trees, with opposite leaves and glandular on both sides, simple hairs, more or less conspicuous collector nerve. Inflorescence in multiflora vertices, arranged in the upper armpits or subterminals, can have 3-15 flowers [9,42]; its distribution is typical from tropical America [9,38,42,43], being the majority of the species, native to the Caribbean and Central America, except the species P. pseudocaryophyllus (Gomes) Landrum LR, which is endemic from Brazil [39,40,44,45].…”
Section: Genus Pimentamentioning
confidence: 99%
“…Furthermore, the best-known species of this genus, due to its economic and pharmacological importance, are P. dioica (L.) Merrill and P. racemosa (Mill.) J. W. Moore [40,41].…”
Section: Genus Pimentamentioning
confidence: 99%
“…In folk medicine, the leaves of P. pseudocaryophyllus are used to prepare a refreshing drink known for its diuretic, sedative and aphrodisiac actions (Paula et al, 2012). The population of Guaraqueçaba, state of Paraná, Brazil, uses P. pseudocaryophyllus leaves infusion in the form of tea to treat the predisposition to arthritical and gouty affections of the joints, fever and other diseases (D'Angelis and Negrelle, 2014).…”
Section: Introductionmentioning
confidence: 99%